Ultra‐Flexible Giant Magnetoresistance Biosensors for Lab‐on‐a‐Needle Biosensing. Issue 7 (12th January 2023) - Su, Diqing; Wu, Kai; Srinivasan, Karthik; Nemati, Zohreh; Zamani, Reza; Chugh, Vinit; Saha, Renata; Franklin, Rhonda; Modiano, Jaime; Stadler, Bethanie; Wang, Jian‐Ping
Abstract: Flexible biosensors exhibit great potential for the detection of various biomarkers with the ability to adapt to different surface textures. Here, a lab‐on‐a‐needle biosensing platform based on ultra‐flexible giant magnetoresistance (GMR) biosensors is developed. The fabricated flexible GMR sensors exhibit a MR ratio of 5.2% and a sensitivity of 0.13%/Oe in the linear region, which are comparable to their rigid counterparts. It is found that the magnetic properties of the flexible GMR sensors remain unchanged after 500 cycles of compressive and tensile stress, indicating strong robustness even when applied to a surface that is constantly in motion. The developed platform is then employed for the detection of different concentrations of canine osteosarcoma (OSCA‐8) cells with a limit of detection (LOD) of 200 cells in 20 µL sample (10 4 cells per mL), which demonstrate the ability to perform real‐time, sensitive, and quantitative cell detection. Abstract : Flexible magnetoresistance biosensors are developed for cell detection. The device has a minimum bending radius of 1 mm and exhibits comparable performance as its rigid counterparts. Real‐time cell detection is realized by wrapping the flexible sensor onto a glass pipette and inserting it into cell samples marked with magnetic nanowires. A LOD of 200 cells in the sample is observed.